12th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference and 14th AIAA/ISSMO Multidisciplinary Analysis And 2012
DOI: 10.2514/6.2012-5684
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Benefits Assessment of Traffic Aware Strategic Aircrew Requests (TASAR)

Abstract: While en route, aircrews submit trajectory change requests to air traffic control (ATC) to better meet their objectives including reduced delays, reduced fuel burn, and passenger comfort. Aircrew requests are currently made with limited to no information on surrounding traffic. Consequently, these requests are uninformed about a key ATC objective, ensuring traffic separation, and therefore less likely to be accepted than requests informed by surrounding traffic and that avoids creating conflicts. This paper st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The results of the benefits analysis indicated that aircraft equipped with TASAR capabilities could reduce flight travel time from one to four minutes and fuel burn by 50 to 550 pounds. 15 To verify and mature the TASAR concept, as well as facilitate its use by operators in the near-term, the TASAR project developed a software automation prototype system, the Traffic Aware Planner (TAP) software application. 5,6 TAP software development has followed an iterative process, expanding and refining TAP's design and capabilities over a series of simulation experiments and flight trials, 8 including:…”
Section: Tasar Conceptmentioning
confidence: 99%
“…The results of the benefits analysis indicated that aircraft equipped with TASAR capabilities could reduce flight travel time from one to four minutes and fuel burn by 50 to 550 pounds. 15 To verify and mature the TASAR concept, as well as facilitate its use by operators in the near-term, the TASAR project developed a software automation prototype system, the Traffic Aware Planner (TAP) software application. 5,6 TAP software development has followed an iterative process, expanding and refining TAP's design and capabilities over a series of simulation experiments and flight trials, 8 including:…”
Section: Tasar Conceptmentioning
confidence: 99%
“…9 A fast-time simulation model using an application programing interface to the Future Air-TrafficAmerican Institute of Aeronautics and Astronautics Management Concept Evaluation Tool (FACET) 10 was implemented and used to analyze historically flown trajectories in comparison to optimized trajectories using a TASAR capability for making trajectory-change requests to ATC. The platform included models for airborne surveillance, conflict probing, flight optimization, aircrew requests, ground surveillance, and ATC evaluation/response.…”
Section: B Preliminary Benefits Assessmentmentioning
confidence: 99%
“…Additionally, the development of TAP considered certification for operational use 6,7 . Furthermore, analyses show the preliminary benefits that TASAR would provide for an air carrier 8 . The benefits study and discussions between the TASAR team members and several domestic airlines resulted in two airlines expressing interest in equipping their aircraft with TASAR technology.…”
Section: Introductionmentioning
confidence: 99%